RUNX2 promotes gastric cancer progression through the transcriptional activation of MGAT5 and MMP13 - Wang, Ying; Tan, Zhibo; Li, Xiaoyu; Zhang, Lili; Pei, Xiaojuan (Frontiers in Oncology, 2023)
RUNX2 is overexpressed in gastric cancer but the mechanism(s) through which it promotes tumor progression remain undefined. Here, we investigated the role of RUNX2 on gastric cancer pathogenesis at the molecular level. The qRT-PCR and western bolt were utilized to examine the mRNA and protein levels. CCK-8, Transwell and wound healing assays were used to measure cell proliferation, invasion and migration. CHIP-PCR gel electrophoresis was used to verify RUNX2 as a transcription factor for MMP13 and MGAT5. The in vivo assay was utilized to assess tumor growth. In vivo assay was used to evaluate tumor growth, aberrant expression of RUNX2 and lung metastasis of gastric cancer. RUNX2 is overexpressed in MKN-45 and AGS cells. Genetic RUNX2 silencing reduced the proliferation, invasion and migration of MKN-45 and AGS cells. Analysis of the gastric cancer samples from the database revealed a significant positive correlation between MGAT5, MMP13, and RUNX2 expression. JASPAR analysis revealed that there was a potential binding site of RUNX2 in the promoter regions of MGAT5 and MMP13, and the experimental results confirmed that RUNX2 could regulate the expression of MGAT5 and MMP13 respectively. In vivo assays confirmed the aberrant expression of RUNX2 in mouse models of gastric cancer and reduced growth and lung metastasis in RUNX2 silenced xenograft tumors assessed. Collectively, these data reveal that RUNX2 enhances MGAT5 and MMP13 expression in gastric cancer cells and represents a biomarker and potential therapeutic target for gastric cancer therapy.